The Study of Exercise Behavior of Staffs in Phra Nakhon Si Ayutthaya Provincial Public Health Office - เลาหภิชาติชัย วิมล (Journal of Preventive Medicine Association of Thailand, 2019)
The purpose of this research was to study exercise behavior of staffs in Phra Nakhon Si Ayutthaya Provincial Public Health Office. The study design was one group pre-test and post-test design. The study samples were 50 staffs who were willing to enroll in this study. The samples were selected by purposive sampling from the staffs in Phra Nakhon Si Ayutthaya Provincial Public Health Office. The body mass indexes of the samples were 25 kg/m2 or over. The waistlines of men were more than 90 cm. and women were more than 80 cm. Stage of Change Theory was applied in this study. The research instruments were knowledge attitude and exercise behavior questionnaires. The data were collected 1 week before and after applying the program. Percentage, mean, standard deviation and dependent samples t-test were applied for data analysis. The results indicated that after participating in the exercise behavior modification program, the staffs had significantly better knowledge, attitude and practice on exercise behavior than before participating in the exercise behavior modification program at the 0.05 level. They also had significantly lower body mass indexes and the waistlines than before participating in the exercise behavior modification program at the 0.05 level. Therefore, exercise behavior modification program should be applied for enhancing exercise behavior of staffs in Phra Nakhon Si Ayutthaya Provincial Public Health Office.